Adenocarcinoma with Mixed Subtypes in the Early and Advanced Gastric Cancer - Xixian Zhao; Yizhang Li; Zhenwei Yang; Hailin Zhang; Hongling Wang; Jun Lin; Jing Liu; Qiu Zhao (Canadian Journal of Gastroenterology and Hepatology)
Objective. Adenocarcinoma with mixed subtypes (AM) is a histological classification based on the WHO classification. We aimed to compare the prognosis among AM, classic adenocarcinoma (CA), mucinous adenocarcinoma (MAC), and signet-ring cell carcinoma (SRCC) in early and advanced gastric cancer (EGC and AGC), respectively. Methods. The Surveillance, Epidemiology, and End Results (SEER) database was queried from 2001 to 2016. Univariate and multivariate Cox analyses were performed to compare prognosis between AM and histologic subtypes of CA, SRCC, and MAC in ECG and ACG. A nomogram was established to predict the cancer-specific survival (CSS) of gastric cancer (GC) patients with AM. C-index, calibration curves, and receiver operating characteristic (ROC) and decision curve analysis (DCA) curves were applied to examine the accuracy and clinical benefits. Results. In the prognosis among these four histological subtypes in EGC patients, there are no differences. For AGC patients, AM had a significantly poorer prognosis compared with CA and MAC (P=0.003, 0.029) but similar prognosis to SRCC. A nomogram based on race, T stage, N stage, M stage, and surgical modalities was proposed to predict 1- and 3-year CSS for GC patients with AM (C-index: training cohort: 0.804, validation cohort: 0.748. 1- and 3-year CSS AUC: training cohort: 0.871 and 0.914, validation cohort: 0.810 and 0.798). 1- and 3-year CSS DCA curves showed good net benefits. Conclusions. EGC patients with AM had similar survival to those with CA, MAC, and SRCC. AM was an independent predictor of poor prognosis in AGC. A nomogram for predicting the prognosis of GC patients with AM was proposed to quantitatively assess the long-term survival.